STRATEGI GURU TERHADAP PENGEMBANGAN KECERDASAN SPIRITUAL ANAK TUNAGRAHITA MELALUI PEMBIASAAN DI SLB BHAKTI PUTRA PALU - Aris Efendi; Fatimah Saguni; Suharnis (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to examine the teacher's strategies in developing the spiritual intelligence of children with intellectual disabilities through habituation methods, as well as to analyze the impact of implementing those strategies on students' spiritual development at SLB Bhakti Putra Palu. This research employed a qualitative approach with a case study design. Data were collected through participatory observation, in-depth interviews, and documentation study, then analyzed using the interactive analysis model of Miles, Huberman, and Saldaña, and validated through source triangulation and technique triangulation. The findings reveal that teachers implemented five adaptive and relational habituation strategies, encompassing daily worship habituation, direct exemplary conduct, greeting and courtesy habituation, positive reinforcement, and continuous communication with parents. These strategies were carried out consistently without a formal written program, yet proved effective in producing tangible changes in students' spiritual behavior. The identified impacts include improved discipline in worship routines, the emergence of spontaneous greeting behavior, the development of empathy and social awareness, increased independence in basic worship practices, and the establishment of emotional stability among students with intellectual disabilities. This study affirms that the effectiveness of spiritual intelligence development in children with intellectual disabilities is not determined by the completeness of program administration, but rather by the depth of pedagogical relationships and the consistency of habituation built into daily practice. These findings contribute to the achievement of SDG 4 on quality and inclusive education, particularly in strengthening dignified spiritual education services for children with special needs in Special Education Schools.